The Study of the significance of Fintech to the development of risk management - TANG, TIANYU (2017)
This dissertation aims to explore the significance of Fintech to the development of risk management. In order to reach this research objective, the process of the research is designed to compare the risk values between Fintech companies and traditional financial institutions. The secondary data is collected from a database and is tested through independent samples t-test in SPSS. The result comes out that there is no distinct effect of Fintech on the development of risk management. There are three possible reasons to illustrate this outcome. Firstly, the entire effect of Fintech is not clearly shown might because the effects on risk management are eliminated mutually between Fintech and new risks. This can be illustrated that Fintech has positive effect on risk management through building new system while it can also bring new risks, which makes no effect on risk management as a whole. Secondly, the declined importance of credit risk might be one of the reasons that lead to no effect on risk management for Fintech as other risks might have more effect occupying the significant position of credit risk in financial industry. Thirdly, many Fintech companies seek for popular technology that might be not appropriate with current business. This might lead to barriers of development of technology as well as the risk management. Although the result shows no distinct effect of Fintech on risk management, Fintech is still expected to develop well with a number of opportunities.